2013
DOI: 10.1186/1471-2261-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension is associated with increased carotid atherosclerotic plaque in the community population of Southern China

Abstract: BackgroundThe proceeding of blood pressure (BP) from normal level to the hypertension has been found to be associated with increased cardiovascular events and multiple vascular risk factors. However, whether the process is associated with increased carotid atherosclerotic plaque per se or not is still unclear.MethodsNine hundred and forty-two participants aged from 46 to 75 were enrolled from community population in Southern China. Their metabolic risk factors, carotid intima-media thickness (cIMT) and atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…To compare our results with previous studies, we searched PubMed to identify population‐based studies that reported the prevalence of CA detected by ultrasound in China, and summarized findings are shown in Table 4. Of these previous studies,16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26 only the CKB (China Kadoorie Biobank) study included a large sample of participants (N=24 822) from multiple geographic regions in China16; all other studies were geographically local. The CKB study reported that the overall prevalence of carotid plaque was 31%, which was much higher than the prevalence of 13.9% in the present study; however, the CKB study included participants with stroke (5.4%) or coronary heart disease (7.5%).…”
Section: Discussionmentioning
confidence: 99%
“…To compare our results with previous studies, we searched PubMed to identify population‐based studies that reported the prevalence of CA detected by ultrasound in China, and summarized findings are shown in Table 4. Of these previous studies,16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26 only the CKB (China Kadoorie Biobank) study included a large sample of participants (N=24 822) from multiple geographic regions in China16; all other studies were geographically local. The CKB study reported that the overall prevalence of carotid plaque was 31%, which was much higher than the prevalence of 13.9% in the present study; however, the CKB study included participants with stroke (5.4%) or coronary heart disease (7.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, a chronic disease with a high prevalence not only in Asia but also worldwide [ 14 ], is closely associated with metabolic risk factors such as obesity, insulin resistance, and abnormal lipid profiles in adults [ 15 , 16 ]. In addition, pre-hypertension has a high prevalence in Asia [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between structural alterations of carotid artery and the development of CVD has drawn interests, only two studies examined the association between the carotid artery and pre-hypertension [ 15 , 23 ]. Furthermore, the previous two studies showed different results in terms of the relationship between prehypertension status and IMT.…”
Section: Introductionmentioning
confidence: 99%
“…For example, FMO1 (p=9.81e-5) is a risk gene of cardiovascular disease [Mendelsohn and Larrick 2013], which is usually associated with hypertension. Another susceptible gene is AGBL1 (p=8.16e-4), which is associated with carotid plaque [Dong, et al 2012], and prehypertension is associated with significantly increased carotid atherosclerotic plaque [Hong, et al 2013]. We also report long-term depression pathway (p=4.21e-6) as a significant pathway.…”
Section: Resultsmentioning
confidence: 76%